Commission of online travel agent to increase room occupancy at The-Ritz-Carlton, Bali - Made Ayu Krismasari; I Ketut Astawa; Ni Nyoman Triyuni (International Journal of Green Tourism Research and Applications, 2020)
Purpose: This study focuses on analyzing the commission given to online travel agent to the room occupancy at The Ritz-Carlton, Bali. The purpose of this study are to analyze the contribution of the commission of online travel agent to the room occupancy and find out which OTA that contributed the most to the room occupancy at The Ritz-Carlton, Bali. Research methods: The methods of data collection applied for this research are observation, interview, documentation, and literature study. The data analysis techniques used are quantitative analysis techniques analyzed using SPSS Program to find out the influence of the commission given to OTA and qualitative descriptive analysis to interpret data information through words. Results and discussions: The results showed that the commission for OTA contributed to the room occupancy and there was a positive and significant influence partially by giving commission to Agoda.com with Sig. value 0.029, Booking.com with Sig. value 0.020, CTRIP with Sig. value 0.018, and Expedia with Sig. value 0.014 to the room occupancy at The Ritz-Carlton, Bali. Besides, simultaneously by giving commission to Agoda.com, Booking.com, CTRIP, and Expedia positively and significantly influences the room occupancy with Sig. value 0.00. Those OTA give contribution about 56.6 percent toward the room occupancy at The Ritz-Carlton, Bali. The OTA that contributed the most in affecting the room occupancy is Expedia with the smallest significant value at 0.014. Expedia's room production directly contributes greatly to increasing room occupancy at The Ritz-Carlton, Bali because the percentage of commission fees to Expedia is effective as a motivation to provide high room production and also consistently increases every year. Implications: The suggestion given to management is the commission to each OTA needs to be evaluated more to maximize room occupancy as not to burden the hotel expenses.